Las cosas: Entre el delirio de tener y la fuga del ser (2016)
Reading of The Things. A story from the sixties’ by French writer Frances Georges Perec, it is a literary tour of the life of a Parisian couple surrounded by a consumeristic society in which they are paradoxically immersed. In this article, the author examines the idea of everydayness from a sociological point of view, claiming that the symbolic universe that Jerome and Sylvie find themselves in is the product of their social context. Also supported, is the idea that the everydayness that the couple find themselves confronted with, transforms the meaning that the characters give to their lives. Their symbolic universe revolves around the material aspects marked by the trends of the well-off society of the time, where the notion of material possessions is bound to emotional stability and total happiness. The notion of everydayness sways from an imaginary material world made up of all the objects that the couple wish to have, to the actual vacuous and superficial reality they have to withstand on a daily basis.